Present understanding of currents and events at Ormen Lange - Alendal, Guttorm; Berntsen, Jarle; Furnes, Gunnar (Zenodo, 2002)
The exploration of the Ormen Lange gas field represent new challenges to design, deployment installation and maintenance. In addition, the gas field is located at the scene of one of natures most extreme events, the Storegga landslide. The topography at Ormen Lange is extremely rough, which not only limits the corridor of the pipeline, such extreme terrain may also produce extreme current events. The suggested work plan to determine the tail of current distribution involves theoretical studies, laboratory experiments, in-situ measurements, and numerical simulations. The interface between the Atlantic and the much colder Norwegian Sea Arctic Intermediate waters often passes through the Ormen Lange area. The high density gradient present through such an interface leads to complex dynamics. Use of realistic temperature and salinity profiles are important for proper initialization of the models used in the studies. So far, profiles lack the strong pycnocline often present in the area . The rough topography generate dynamics that are important on all scales. Rough topography generate form drag that is important for regional modeling. To build a reliable forecast system it is crucial to study this effect and incorporate it into the regional model system. One necessary exercise, in order to establish such a parameterization, is to establish statistical characteristics of the topography at Ormen Lange, such as mean, standard deviation, and moments from the anisotropy tensor. NERSC Technical Report no. 229.